Caught in the act: Femtochemistry opens the lid on biology‧s third vital criterion. (11th December 2012) - Hunter, Philip
Abstract : Femtobiology freeze‐frames crucial split seconds of chemical reactions to investigate how enzymes function. The potential prize from this knowledge could be new avenues for drug development or ways to produce clean energy.